The experiences of postgraduate psychology students regarding the development of multicultural competence - Bodenstein, L.; Naudé, L. (South African Journal of Higher Education, 2017)
This study investigated the experiences of postgraduate psychology students regarding their multicultural competence development (MCCD). King and Baxter Magolda’s multidimensional framework for the development of intercultural maturity, comprising cognitive, interpersonal and intrapersonal dimensions served as theoretical grounding. A qualitative, case study design was employed, using thematic analysis to analyse focus group data. It was found MCCD takes place across the lifespan and in various contexts. Methods to overcome obstacles to MCCD were identified, as well as the participants’ positions of MCCD. Lastly, educational experiences that promote MCCD are discussed.